Theoretical Study of the Coordination of Semicarbazone and Its Methylated Derivatives - KUEVI, URBAIN AMAH; KPOTIN, ASSONGBA GASTON; ATOHOUN, YACOLÈ GUY SYLVAIN; MENSAH, JEAN-BAPTISTE (My University, 2018)
Semicarbazone is a molecule with a group R1R2C=N-NR3-C(=O)-NR4R5. The oxygen atom has two free electron pairs; each nitrogen atom has one free electron pair. These free electron pairs are potential sites of coordination. The simplest molecule in this series is the semicarbazone which the formula is H2C=N-NH-C(=O)NH2. By replacing the oxygen atom by a sulfur atom is obtained a thiosemicarbazone. Some semicarbazones, such as nitrofurazone, and some thiosemicarbazones are known to have many properties: antiviral, antibacterial, antitrypanosomal, anticonvulsant, antitumor, anticancer. They are usually mediated by an association with copper or iron. Indeed transition metal complexes with given chemical structures are useful alternatives in the treatment of certain diseases since coordination of active ingredients deeply modifies both the physiological properties of metals and ligands in the meaning of overall improvement of these properties. The present work focuses on quantum study of the complexation of semicarbazone and its methylated derivatives. The purpose of this study is to determine the most favorable coordination site of each of these ligands. It was found that the oxygen atom appears more favorable to the coordination of semicarbazones. Complexes of these ligands with the Zn (II) were modeled. The calculations were made by the method DFT / B3LYP with the orbital basis 6-31G (d, p).
Keywords: coordination compounds; semicarbazones; DFT/ B3LYP; 6-31G (d; p) basis set